A nanoparticle‐coupled T2 peptide induces immune tolerance and ameliorates chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) in mice model. (11th January 2019) - Cao, Yanfang; Cheng, Yijie; Ihsan, Awais Ullah; Khan, Farhan Ullah; Xie, Dianyou; Cui, Xingxing; Wang, Wenlu; Zhou, Xiaohui
Abstract: Chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) is a complex disease of unclear etiology. Precise treatment of CP/CPPS is not available due to lack of specific cause; however, autoimmunity is the most valid theory. We develop a new treatment strategy that involves synthesis and coupling of biodegradable nanoparticles to antigenic T2 peptide to induce immune tolerance in CP/CPPS mice models. A total of 50 male C57BL/6 mice were randomized into five groups, that is, naïve, Model, PLGA‐PEMA, PLGA‐PEMA‐OVA323‐339, and PLGA‐PEMA‐T2 group. All groups except naïve were injected subcutaneously on day 0 with 0.2 mL of T2 peptide with CFA to generate valid CP/CPPS models. After successful induction of CP/CPPS, Model group, PLGA‐PEMA, PLGA‐PEMA‐OVA, and PLGA‐PEMA‐T2 groups were treated with 0.15 mL of normal saline, 0.2 mg of PLGA‐PEMA and PLG‐PEMA‐T2 and 0.3 mg PLGA‐PEMA‐OVA nanoparticles, respectively, on day 28. Hematoxylin and eosin staining, and ELISA were used to evaluate the variation in CP/CPPS manifestations and seral level of IL‐10 in each group. Pain threshold and voiding behavior were also recorded for every group. Mice treated with PLGA‐PEMA‐T2 exhibited enhanced pain threshold, reduced urine frequency, and prostate pathology. Furthermore, serum level of inflammatory mediators (TNF‐α and CRP) were reduced and anti‐inflammatory IL‐10 was enhanced in PLGA‐PEMA‐T2 group as compared to other groups. Our results demonstrate that PLGA‐PEMA‐T2 nanoparticle ameliorates disease manifestations in CP/CPPS mice models and upregulates IL‐10 which is essential for tolerance induction. This strategy highlights the new therapeutic approach utilizing biodegradable nanoparticles for the treatment of CP/CPPS.